Spatio-temporal variance and urban heat island in Akure, Nigeria: a time-spaced analysis using GIS techniqu - Popoola, Olusola; Durojaye, Peters; Bayode, Taye; Popoola, Ayobami Abayomi; Olanibi, Julius; Aladetuyi, Olamide (South African journal of geomatics, 2020)
The threat of the increasing global temperature is now of global concern than ever before. This prompted the authors to gain insights on the Urban Heat Island (UHI) phenomenon in a medium-sized city of Akure, Nigeria. A random sampling of three hundred and twenty-five (325) structured questionnaires was administered and analyzed with the aid of the Statistical Package for Social Sciences (SPSS). Landsat satellite imagery for the years 2000; 2007; 2013 and 2018 were acquired and used for the computation of land use-land cover (LULC) and the Land Surface Temperature (LST) of the study area using ArcGIS 10.5. Between the years 2000 and 2018, built-up area increased by 8.78% at the expense of the non-built up land use. The residents were aware of UHI and climate change but characterized by superficiality. The study recommends a community awareness program on the menace of climate change and the integration of climate education into the curriculum of schools and other institutions of higher learning.
Elektronische Ausgabe der Druck-Ausgabe
Gesehen am 15.12.2025